Investigação teórica da utilização do dendrímero de poliamidoamina (PAMAM) para o transporte e liberação do fármaco doxorrubicina - Oliveira Sobrinho, Handriela Hoff de (2022)
One of the methods of treating cancer is the use of chemotherapy drugs, as they are toxic to cancer cells, but in many cases they have low specificity and high toxicity, also affecting healthy cells in the body. Doxorubicin is one of these drugs effective in the treatment of cancer, but with toxicity to the cardiovascular system. An active drug targeting by a nanoparticle system can provide a precise treatment with possible reduction of side effects. This work describes the electronic and structural properties of the interactions that occur in a nanoparticle system with potential drug delivery through computational simulations ab initio, based on the density functional theory, using the SIESTA code, in which the formation energy is evaluated , energy levels and charge density. The delivery system is formed by a PAMAM dendrimer molecule (G0), the drug doxorubicin (DOXO) and two targeting molecules, folic acid (FA) and cis-aconitic acid (CIS). The interactions are understood by stages of structure complexity, starting with the interaction of only the PAMAM dendrimer and doxorubicin (G0-DOXO), followed by the PAMAM dendrimer acetylated and conjugated to folic acid with doxorubicin (G0.NHAc.FA-DOXO) and concluding with the acetylated PAMAM dendrimer, conjugated to folic acid interacting with doxorubicin linked to cis-aconitic acid (G0.NHAc.FA-DOXO.CIS). The proposed structures were submitted to three models of interaction position to verify the formation of hydrogen bonds, and no restrictions were applied to atoms and spins during the optimization. From the results, it was observed that in all structures and models there was no significant load transfer. Connection distances are on the order of 2.5 Å. Negative formation energies were obtained, indicating the formation of stable transport systems. The position of the HOMO and LUMO energy bands in the same structure in the three models remained similar, generating a constant energy gap, however, above the HOMO orbital and below the LUMO orbital, the positions of the electronic bands were different from a model to the other, demonstrating the presence of interactions. The charge density showed that in the transport system the charge density of the HOMO orbital comes from the dendritic system and the LUMO orbital comes from doxorubicin, except for Model 2 of the G0.NHAc.FA-DOXO.CIS structure, in which both the doxorubicin and dendrimer showed charge density in the HOMO orbital. According to these results; it is possible to confirm the formation of hydrogen bonds between PAMAM dendrimer and doxorubicin, which indicates a promising system for selective and specific drug transport in which it would contribute to the reduction of its toxicity and the precision of the treatment.